If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y = -2(x + 1)(x + -5) Reorder the terms: Y = -2(1 + x)(x + -5) Reorder the terms: Y = -2(1 + x)(-5 + x) Multiply (1 + x) * (-5 + x) Y = -2(1(-5 + x) + x(-5 + x)) Y = -2((-5 * 1 + x * 1) + x(-5 + x)) Y = -2((-5 + 1x) + x(-5 + x)) Y = -2(-5 + 1x + (-5 * x + x * x)) Y = -2(-5 + 1x + (-5x + x2)) Combine like terms: 1x + -5x = -4x Y = -2(-5 + -4x + x2) Y = (-5 * -2 + -4x * -2 + x2 * -2) Y = (10 + 8x + -2x2) Solving Y = 10 + 8x + -2x2 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Simplifying Y = 10 + 8x + -2x2
| (3x-2)/10-(4x+1)/4=-4 | | iz^2-4iz+4i=8 | | f=.5kq | | -.01+60=0 | | -5s=-30 | | x^2+8x=9x+42 | | .01+60x=100 | | -60-1x=100 | | (5x+46)^1/2=3x+12 | | z^2-16z+64=-256 | | 5b-3-9b-7= | | (9X+45)^1/2=2X+8 | | (5X+24)^1/2=3X+16 | | (5X-24)^1/2=3X+16 | | 3(k+4)-8k+4+2= | | -(11x-5)-(2x-6)+6=-6(x-1)-(12x+7)+3 | | (-4/5)/(3/2) | | c-3c= | | -4/5/3/2 | | -5(4y-6)+4(2y+6)= | | 6(3y+7)+(-28y)= | | y^2=-6x+5 | | 2x^2(x+3)=-4x^2(x-1) | | 17+5(6c-3)= | | 12(3x+3)-6(2x-5)=4x-54 | | 40-[4+8y-3(y+2)]=-3(5y-7)-[8(y-1)-13y+17] | | 40-[4+8y-3(y+2)]=-3(5y-7)-[8(y-1)-13y+13] | | 26=5(x+6)-7x | | 11=3(x-3)-(x-6) | | -2k+3k-5+5k= | | 7x-3x-18=2 | | 9x+1=7x+31 |